Aspects of the biology and ecological requirements of the Lake Huron tansy (Tanacetum huronense Nutt.): implications for the conservation of a threatened species. - Trexel, Dawn (1998)
The Lake Huron Tansy (Tanacetum huronense, Compositae) is a perennial that lives on the dunes of the Great Lakes, Hudson Bay and the Pacific Northwest (Voss, 1996). Due to threats to its habitat, the Lake Huron Tansy's survival is at risk. Increased development along lake shores as well as elevated amounts of foot and vehicular traffic along beaches and dunes jeopardize the existence of the species. It is listed as a threatened species by the state of Michigan. According to D'Ulisse and Maun (1996), preservation and restoration of rare plant species relies on the knowledge of the crucial factors that limit the reproduction, germination, survival, and growth of the plant. Very little is currently known about these aspects of the Lake Huron Tansy. The objective of my study was to attempt to answer some of the questions concerning the biology of this plant in an effort to better understand the requirements needed to reestablish this plant in suitable habitats and to de-list it as a threatened species. http://deepblue.lib.umich.edu/bitstream/2027.42/54815/1/3256.pdf Description of 3256.pdf : Access restricted to on-site users at the U-M Biological Station.